Projeto e implementação de um piloto automático aplicado a aeromodelos de asa fixa e asa móvel - Alves, Rubens Antônio (2015)
This Project, in the electrical engineering area, consists in the development of a complete control system, hardware and software, for controlling model airplanes of the fixedwing and rotary-wing types, aiming the implementation of an automatic control system compatible with the necessity of autonomous and aided flights, applied to critical systems monitoring.The final system consists of a controller, or automatic pilot, with specific hardware and software, capable of controlling a model airplane using GPS coordinates, in a way that allows the airplane to go through a planned route and go back to the starting point in an autonomous way. The controller should receive, in ground, the programmed route; the model should answer to the pilot commands, within a visual range when operating in the aided mode, and should go through the programmed route in the autonomous mode, after confirmation of the pilot. After reaching the end of the programmed route, the model airplane should return to the starting point, keeping the maximum flight level of the route as the reference height. The model airplane will carry in a communication system to allow the monitoring process from a ground station, able to keep updated the airworthy conditions, as well as the level of accuracy between the actual and the planned route. The communication may be carried out directly using a radio link, with the receiver allocated in a mobile ground station, monitored by a pilot, to make higher the security level. However, the model airplane may transfer the data through a GPRS link, connected to the web system, which transfers the data to the ground station. In this case, the ground station must be connected to the web.The route saved in the model control system is built based on online maps directly linked by the software for the mission programming and monitoring, which can carry out the treatment and storage of the model data and parameters. The programming of the stability control and route, with primary data of latitude, longitude and height allows the real time monitoring of the model, related to the planned route and throught images captured by embedded video cameras. All data are storage following a timeline process, such that they can be recovered for futher analysis.